The role of economic freedom in the development of international tourism in Asian countries - Dang, Buu Kiem; Dang, Thanh Thuc (Universitas Islam Indonesia, 2024)
Purpose ― This paper aims to investigate the influence of economic freedom and its components, namely business freedom and trade freedom, on international tourist arrivals in Asian countries. Additionally, it examines the effect of important macroeconomic factors, such as foreign direct investment, exchange rates, political stability, GDP per capita, and inflation on international tourist arrivals in Asian countries.Methods ― The GMM two-step estimation system is used to analyze data from 25 Asian countries from 1995 to 2020.Findings ― The results show that economic and trade freedom positively influence tourism, while business freedom has a less distinct impact. Inflation positively contributes to tourist arrivals. Exchange rates and political stability show inconclusive effects.Implications ― The study recommends that governments prioritize expanding economic freedom to boost international tourism.Originality ― This is the first study on the impact of economic freedom on developing international tourism in Asian countries.